Viability of the public pension system in Spain - de Espínola, José Ramón (Razón y fe, 2018)
This article analyses demographic and economic factors that unbalance the Spanish public pension system. The weak birth rate and the growing life expectancy which in turn cause the ageing of the population, and the Spanish economic growth pattern, that creates few and low productivity jobs, lead to the financial imbalance of the public pensions and to a progressive and unyielding cut of such pensions. To solve this situation, the article holds that a set of economic and social policy measures (and a cultural change in the Spanish society) could avoid it, within these measures it highlights those that change the growth pattern (making it possible to create more and better employment), measures that increase participation of the whole population in the working life (but particularly women and the elderly), likewise, an intelligent immigration policy could prevent the progressive and inexorable Spanish public pensions cutback.
Keywords: public pensions; demographic ageing; growth pattern; model of production; employment